Belajar dalam Perspektif Islam - Sakilah Sakilah (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Learning is the key to the most urgent in any educational endeavor. Without learning education will never be realized as a process, in which the process is an emerging behavior and always improved through a series of reactions to situations and stimuli that exist. It is therefore very important in the study of human development, by studying humans become more mature and more perfect. Besides learning can be understood as a phase change in the whole of human behavior are relatively sedentary as experience and interaction with the environment that involve physical maturation process. The concept of learning in Islam is not only to meet the needs and development of rational only, but should include the entire physical and spiritual needs in a balanced way, do not see the psychological elements are dichotomous. This concept actually gave birth fikir and remembrance into one direction, and put a man in accordance with human dignity, both as individuals, social or spiritual beings in the learning process while Islam has occurred since the creation of Adam and lowered it to the face of the earth. In the perspective of learning Islam is an obligation for every individual believer to acquire knowledge in an effort to improve the lives of human being life. Methods of learning in the Islamic concept of the imitation, practical experience (trial and error) and thinking.